Rights, centers, and peripheries: experimental moves in Japanese Buddhism - Starling, Jessica (International journal of Dharma Studies, 2017)
In this paper I examine how the Japanese True Pure Land Buddhist school (Jodo Shinshū or Shin Buddhism) has attempted to come to terms with the position of temple wife (bomori), which has historically been a local position based solely on marriage ties to the resident priest of a temple, in a way that accommodates the modern principles of individual rights and freedom of religion. The central Jodo Shinshū institutions of the Otani-ha and Honganji-ha have responded to demands to recognize the autonomous choice of temple wives to undertake a life of service to the parish temple by formulating an initiation ceremony meant to encourage the temple wife's self-awareness as a religious professional. Utilizing ethnographic fieldwork conducted from 2009 to 2013, I survey the various sites where Buddhism is lived and experimented in contemporary Japan. I highlight the interplay between local and central sources of religious meaning and authenticity.